2005–2014 trends of PM10 source contributions in an industrialized area of southern Spain. (May 2018) - Li, Jiwei; Chen, Bing; de la Campa, Ana M.Sánchez; Alastuey, Andrés; Querol, Xavier; de la Rosa, Jesus D.
Abstract: Particulate matter with a diameter of 10 μm or less (PM10) using receptor modelling was determined at an urban (La Linea, LL) and an industrial area (Puente Mayorga, PMY) in Southern Spain with samples collected during 2005–2014. The concentrations of PM10 had been decreasing at both sites in three distinctive periods: 1) the initial PM10 levels approached or exceeded the Spain and EU PM10 annual guidelines of 40 μg/m 3 during 2005–2007 at LL and 2005–2009 at PMY; 2) then PM10 dropped by 25%–∼30 μg/m 3 during 2008–2011 at LL and during 2010–2011 at PMY; 3) since 2012, the PM10 concentrations gradually decreased to <30 μg/m 3 . Chemical compositions of PM10 revealed the important contributions of water soluble ions (sulfate, nitrate, ammonium, and chloride), carbonaceous aerosols, and other major elements. These PM components generally showed a decrease trend, in accord with the trend of PM10 reduction. A PMF model identified seven sources to PM10 contributions. Secondary sulfate, soil/urban/construction dust, and secondary nitrate showed significantly decreasing trends with reduction of 40–60% comparing to the initial levels. The road traffic contribution decreased by 14% from the first to third period. However, sea salt, oil combustion, and industrial metallurgical process had relative stable contributions. These source contribution changes are reasonably governed by the PM emission abatement actions implemented during the past decade, as well as the financial crisis, that accounted for a significant decrease of PM pollution in Southern Spain. The main finding of the work: We identified that the mitigation efforts on industry, fossil fuel combustion, and urban transportation during the past decade were successful for air quality improvement in a highly industrialized area in Southern Spain. Graphical abstract: Image 1 Highlights: PM10 levels decreased during the past decade at urban and industrial areas in Southern Spain. Water soluble ions, organic carbon, major elements, and heavy metals in PM10 were investigated for samples of 10 years. These chemical species showed a gradually decrease trend, in accord with the trend of PM10 reduction. A PMF model identified seven source factors. The reduction in fossil fuel combustion, industry, and road traffic together contributed to the rapid PM10 decrease.